PENYULUHAN TENTANG DEHIDRASI DAN NYERI PUNGGUNG BAWAH PADA KELOMPOK WANITA TANI PUTRI MANDIRI KARANGANYAR - Sumardiyono; Fajariani, Ratna; Setyawan, Haris; Putri, Rachel Alma Syevina; Ratri, Auraningtyas Kurnia; Nurjanah, Fitriyani; Fitriani, Ila; Mahardika, Muiz; Pradetha, Nabila Dean; Widjanarko, Naufal Tio; Muzakki, Pambayun Khairul Rijal; Putranto, Rofi Shiddieq; Azzahra, Syifa (Universitas Mataram, 2024)
Insufficient knowledge regarding hydration, posture, and ergonomic work practices can potentially lead to dehydration and lower back pain among female farmers in Karanganyar. This community service activity focuses on providing education to address these issues. The program aims to educate female farmers on the importance of adequate hydration, maintaining good posture, and performing stretching exercises to prevent dehydration and lower back pain, ultimately promoting their overall health and well-being. This extension activity aims to enhance female farmers' knowledge and understanding regarding the importance of drinking sufficient water, maintaining good posture, and performing stretching exercises. By improving their knowledge and habits, it is expected that female farmers can prevent dehydration and lower back pain. The extension activity was conducted using a combination of lecture, demonstration, and question-and-answer methods. The materials were developed based on a literature review, consultation with a doctor, and considering the participants' educational level. The evaluation was conducted using pre-test and post-test. The follow-up activities of this extension include providing information, submitting data to the Puskesmas (Community Health Center), and reactivating the Pos UKK (Health Promotion Post). A Self-Awareness Survey revealed high-risk hazards among female farmers, including exposure to extreme weather (heat) which poses a risk of dehydration, and repetitive work movements that potentially lead to lower back pain. This extension activity aimed to improve participants' understanding of the importance of drinking water, maintaining good posture, and performing stretching exercises. The participants' understanding scores increased from an average of 70.5 to 82.5, and this increase was statistically significant (p < 0.05). As a follow-up, the community service team provided posters on dehydration prevention and congratulated the Putri Mandiri Karanganyar female farmer group on the reactivation of their UKK Pos activities. Extension activity on dehydration and lower back pain among female farmers of the Putri Mandiri Karanganyar group effectively improved their understanding (p < 0.05).